Incidental learning of semantically transparent and opaque Chinese compounds from reading: An eye-tracking approach. (July 2022) - Yi, Wei; DeKeyser, Robert
Abstract: Using eye-tracking, this study examined the role of semantic transparency in L2 learners' incidental learning of compounds from reading and how real-time processing of novel compounds contributes to vocabulary gains. L2 Chinese speakers encountered 12 novel compounds embedded in stories, each occurring six times. Their knowledge of the compounds was tested immediately after the reading task. Results confirmed the advantage of transparent compounds over opaque compounds (in terms of form recognition and meaning recall), as well as the positive association between reading time summed across exposures and vocabulary gains (in terms of form and meaning recognition, regardless of semantic transparency). Our findings add to the literature on incidental vocabulary learning in that semantic transparency was found to moderate the acquisition order of different aspects of vocabulary knowledge, which highlights the importance of lexical characteristics for future research.